Tuning the Solvatochromic Inversion of Brooker S Merocyanine Analogs - Aliaga-Vidal, C; Aliaga-Vidal, C; Dominguez-Caru, M; Vidal-Palomo, M; Vidal-Palomo, M; Rojas-Figueroa, P (Elsevier B.V., 2023)
The synthesis and spectral behavior of three Brooker s merocyanine (BM) analogs are reported. The solvatochromic effect of the binding position of the phenolate donor group to the pyridinium acceptor ring and the degree of annulation of the acceptor moiety were investigated in pure solvents of varying polarity. All the dyes displayed an inverted solvatochromism. The structural modifications examined modulated the spectral shift ranges in both the negative and positive solvatochromic portions of the general inverted behavior by shortening the former and extending the latter. A second observation, and more remarkable result of the evaluated structural modifications, is the consistent displacement of the solvatochromic inversion point of the dyes toward higher solvent polarities compared to the BM, primarily because of the increase in the dyes sensitivity to the solvent polarizability SP. © 2023 Elsevier B.V.